2009
DOI: 10.1063/1.3072779
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tunneling magnetoresistance of Fe3O4 in a Fe3O4-hexabromobenzene (C6Br6) composite system

Abstract: Magnetotransport of Fe 3 O 4-hexabromobenzene ͑C 6 Br 6 ͒ composite has been studied. Powders of C 6 Br 6 and Fe 2 O 3 nanoparticles were mixed together. They were annealed in hydrogen flow. There was a phase transformation from Fe 2 O 3 to Fe 3 O 4 after annealing. Giant negative magnetoresistance ͑MR͒ was observed at room temperature and the MR ratio is about 13.4% in an applied field of 5 T. The maximum MR ratio is 21.5% at 130 K. The temperature dependence of the resistivity exhibits characteristics of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…They reported a T b = 200 K for the samples. Wang et al reported an MR in 5 T of −21% at 130 K and −13% at 280 K for Fe 3 O 4 nanoparticles dispersed in hexabromobenzene. Wang et al reported an MR in 0.58 T of −17% at 115 K and −7% at RT for OA-covered Fe 3 O 4 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…They reported a T b = 200 K for the samples. Wang et al reported an MR in 5 T of −21% at 130 K and −13% at 280 K for Fe 3 O 4 nanoparticles dispersed in hexabromobenzene. Wang et al reported an MR in 0.58 T of −17% at 115 K and −7% at RT for OA-covered Fe 3 O 4 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…3 Other than the values reported by Poddar et al (MR = −300% at 110 K and −125% above 150 K), 7 such magnitudes have no precedent. MR values of −35% at 60 K, 8 −40.9% at 110 K, 9 −11.5% at 100 K, 10 −21% at 130 K, and −13% at 280 K, 11 −17% at 115 K and −7% at RT, 12 and −25% at 250 K 13 have been reported. The rather large MR observed below 130 K reflects an increase in the resistivity due to the Verwey transition in the Fe 3 O 4 crystal lattice.…”
Section: ■ Introductionmentioning
confidence: 93%
“…To reveal the true spin polarization of Fe 3 O 4 , the reconstruction and the Fe 3+ -rich oxide on the surface should be lifted or removed. We have selected polymers: polystyrene (PS) [90], polycarbonate (PC) [90], poly(methyl methacrylate) (PMMA), [90] fullerene (C 60 ), hexabromobenzene (C 6 Br 6 ) [95], and polytetrafluoroethylene (C n F 2n+2 , also called Teflon) as a coating layer to modify the surfaces of Fe 3 O 4 nanoparticles. These coatings also serve as good insulating barriers between the Fe 3 O 4 nanoparticles.…”
Section: Tunneling Magnetroresistance and Spin Polarization In Fe 3 Omentioning
confidence: 99%